Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
hi
Step-by-step explanation:
Answer:
The true statements are:
the first statement: Systems A and C have the same solution
the fourth statement: System C simplifies to 2x - 3y = 4 and 4x - y = 18
the fifth statement: Systems A and B have different soltuoins.
Explanation:
1) The first statement: systems A and C have the same solutiotn: TRUE
The fourth statement proves that that the two systems are equivalent which means that both have the same solution.
2) The second statement: All three systems have different solutions: FALSE
The fourth statement proves that the systems A and C have same solution, so this second statement is false.
3) The third statement: Systems B and C have the same solution: FALSE
You can solve the two systems and will find the solutions are different
Solution of system B.
3x - 4y = 5
y = 5x + 3
replace y = 5x + 3 in the first equation => 3x - 4(5x + 3) = 5
=> 3x - 20x - 12 = 5
=> - 17x = 5 + 12
=> -17x = 17
=> x = - 17 / 17
=> x = - 1
y = 5x + 3 = 5(-1) + 3 = - 5 + 3 = - 2
=> solution x = -1 and y = -2
Solution of system C.
2x - 3y = 4
12x - 3y = 54
subtract
4) fourth statement: System C simplifies to 2x - 3y = 4 and 4x - y = 18 by dividing the second equation by three: TRUE
Look:
Second equation of system C = 12x - 3y = 54
Divide by 3:
12x - 3y 54
----------- = -----
3 3
Distributive property:
12x 3y
------ - ----- = 18
3 3
4x - y = 18, which is the same second equation of system A, so the system C simplifies to the same system A, which is 2x - 3y = 4 and 4x - y = 18.
5) The fifth statement: systems A and B have different solutions: TRUE
You can solve the two systems and will find the solutions are different
Solution of system A:
2x - 3y = 4
12x - 3y = 54 since it is equivalent to 4x - y = 18
-------------------
12x - 2x = 54 - 4 subtracting the first equation from the secon
10x = 50 adding like terms
x = 5 dividing by 10
From 2x - 3y = 4 => 3y = 2x - 4 = 2(5) - 4 = 10 - 4 = 6
=> y = 6 / 3 = 2
=> x = 5, y = 2
Solution of system B.
3x - 4y = 5
y = 5x + 3
replace y = 5x + 3 in the first equation => 3x - 4(5x + 3) = 5
=> 3x - 20x - 12 = 5
=> - 17x = 5 + 12
=> -17x = 17
=> x = - 17 / 17
=> x = - 1
Which is enough to prove that the two systems have different solutions.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.